Food Insecurity and Coping Strategies of Fishing Communities Living in Lake Victoria, Homa Bay County, Kenya - Ambale, B.; Kiptui, M.; Saina, C. (Africa Environmental Review Journal, 2022)
The fishing communities along the shores of Lake Victoria have developed coping strategies to counter their daily life threatening challenges linked to food insecurity by adopting efficient technologies for food production, distribution, and storage. The study focused on the impacts of food insecurity on the livelihoods of members of the fishing community living on the shores of Lake Victoria, Homa Bay County. The objectives of the study were to investigate factors causing food insecurity and impacts of food insecurity to livelihoods of the fishing communities using descriptive survey research design. A sample population of 399 respondents was utilized and reliability ascertained using Cronbach's alpha coefficient on a pilot study. Data was gathered and analyzed using the Statistical Package for the Social Sciences (SPSS). The findings in multiple-response questionnaire show that major factors causing food insecurity are; climate change (95.6%), unstable fish prices (94.7%), poor fish storage methods (93.0%), rapid population growth (85.0 %), seasonal fishing bans by the government (83.2%) and poverty (76.9%).The impacts of food insecurity on the respondents are; poor health (especially HIV infected), malnutrition and diseases (39.1%), loss of property and (85.2%) and substantial fluctuation in food prices (96.5%). Majority of respondents (96.0%), skipped meals especially lunch; (90.0%) sent their children to work at their neighbors’ farms for pay and (50.9%) practiced farming as alternative coping strategy. This paper concludes that, food shortages and inadequate food storage played a critical role in causing food insecurity. It is recommended that the county government puts up a cold storage facility to reduce post-harvest loses and also provide opportunities for alternative sources of livelihood in order to reduce over dependence on fisheries resources.